Mediación y participación ciudadana en México - María Guadalupe Márquez Algara; José Carlos De Villa Cortés (Universidad Hemisferios, 2016)
This paper describes the origin and development of the mediation in Mexico, a procedure that is currently gaining great force in that country. However, its beginning dating from 1997 had a certain problematic since the mediation did not begin as a national movement, because was local and only in a judicial forum. However, in 2008 it became a federal obligation that all the states of the country offer alternative justice mechanisms, including the mediation in their respective judicial powers, although each state developed its own way, because their respective laws are local, so their results at the individual level are very diverse. Also, in recent years, it has also developed the school, community and indigenous mediation in some states, which promote citizen participation, which is one of the major factors for the development of mediation in such scenarios. The article narrates in a chronological way the described evolution, using, besides doctrine, statistics and official information. Also shows, that though the mediation in Mexico is gathering strength, it is not doing it in a homogeneous way in the whole country because the state differences sometimes are very big.